RILs development and its characterization for MLB resistance and flowering in maize (Zea mays) - KUMAR, BHUPENDER; SINGH, SHYAM BIR; SINGH, VISHAL; HOODA, KARAMBIR SINGH; BAGARIA, PRAVIN KUMAR; KUMAR, KRISHAN; PRADHAN, HANS RAJ; KUMAR, SONU; MEENAKSHI, MEENAKSHI; BHATI, PRADEEP; KUMAR, BRIJESH; CHATURVEDI, GARIMA; et al. (The Indian Journal of Agricultural Sciences, 2020)
Maydis leaf blight (MLB) resistance and days to flowering are the important yield determining traits in maize. Breeding for MLB resistance and days to flowering can be accelerated by understanding their genetics and identifying genomic regions contributing for their expression. Two F2s population with 338 and 349 individuals along with their recombinants inbred lines (RILs) having 283 and 277 individuals were developed from F1 crosses HKIPC4P × CML269 and ESM113 × P72clXbrasil1117 for genetic studies of MLB resistance and flowering. The populations along with their parents were screened under artificially inoculated conditions at hot-spot sites during 2015–17. Race O inoculum was artificially inoculated in the leaf whorl of each plant at 4-6 leaf stage. The inoculation was repeated after 8-10 days of first inoculation to avoid any chance of disease escape. The partial dominance in F1s, normal distribution patterns in F2s and RILs for both the traits has indicated their polygenic nature. Correlation analysis found negative and significant association (P≤0.001) between disease scores and days to flowering across the populations. Total 250 simple sequence repeats (SSR) markers, uniformly selected from all linkage groups were used for parental polymorphism survey between parents of the populations contrasting for target traits. Of total 250 SSRs, 122 (48.8% polymorphism) were identified as polymorphic between either of the parents. Sufficient genetic variation was observed within and between different F2s and RILs mapping populations. The information on inheritance, parental polymorphism survey and genetic materials developed will be useful for fine mapping and systematic breeding of targeted traits in tropical maize germplasm.